On δ-small M-Projective Modules - S. Al-Mothafar, Nuhad; T. Mohammed, Munther (Iraqi Journal of Science, 2023)
In this paper we study the concepts of δ-small M-projective module and δ-small M-pseudo projective Modules as a generalization of M-projective module and M-Pseudo Projective respectively and give some results.